2023
DOI: 10.3892/etm.2023.11875
|View full text |Cite
|
Sign up to set email alerts
|

COL4A1 promotes the proliferation and migration of oral squamous cell carcinoma cells by binding to NID1

Abstract: Collagen type IV α1 chain (COL4A1) is a collagen protein that acts as a tumor-promoting factor in several types of cancer. However, the role and the potential mechanisms involving COL4A1 in oral squamous cell carcinoma (OSCC) remain unclear. Using reverse transcription-quantitative PCR and western blotting, the expression levels of COL4A1 and (nidogen-1) NID1 in OSCC cells were assessed. Cell Counting Kit-8, EdU staining and colony formation assays were used to evaluate cell proliferation. Cell migration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Moreover, upregulation of COL4A1 has been reported in patients with Oral Squamous Cell Carcinoma. [ 34 ] Elevated levels of COL4A1 contribute to enhanced migration, invasion, and proliferation in various cancers, including breast cancer and bladder cancer. Prior investigations have also recognized COL4A1 as a pivotal gene implicated in the initiation, advancement, and recurrence of gastric cancer, [ 35 ] and have associated its overexpression with unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulation of COL4A1 has been reported in patients with Oral Squamous Cell Carcinoma. [ 34 ] Elevated levels of COL4A1 contribute to enhanced migration, invasion, and proliferation in various cancers, including breast cancer and bladder cancer. Prior investigations have also recognized COL4A1 as a pivotal gene implicated in the initiation, advancement, and recurrence of gastric cancer, [ 35 ] and have associated its overexpression with unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of COL4A1 can promote the proliferation of colon tumor cells and may be a target to inhibit the proliferation of colon tumor cells.However, the mechanism by which COL4A1 inhibits tumor cell proliferation remains unclear.Nidogen-1(NID1) is a component of the extracellular matrix and the basement membrane [40].The main function of NID1 is to provide a link between laminin, collagen, proteoglycans and cell surface receptors to control cell polarization, migration and invasion [41]. Tian et al showed that COL4A1 promotes the proliferation of oral squamous cell carcinoma by binding to NID1 [42].…”
Section: Disscussionmentioning
confidence: 99%
“…Immunostaining showed that the localization of MMP14 is also p turbed by TKS4 deletion, as the protein was more precisely located around the nucleu the TKS4 KO cells, with a decreased protein level compared to MMP14 observed in spindles (invadopodia and podosome) of WT cells (Supplementary Figure S8). According to the transcriptomic analysis, a noticeable elevation could be observed in the expression of most of the invasion marker genes (Figures 3B and S3B), such as urokinase-type plasminogen activator (PLAU) [65], laminin genes (LAMA3, LAMA5) [66][67][68], collagen-related genes (COL1A1, COL4A3, and COL6A2) [69][70][71][72], cathepsin genes (CTSA, CTSB) [73][74][75], serpine1 (PAI-1) [76], MMP genes (MMP7, 9, 13, 14, and 17) [77][78][79][80][81], and integrin-related genes (ITGA2, ITGA3, and ITGB4) [82][83][84]. The analysis also revealed that over 85% of recognized invasion markers undergo alterations upon TKS4 deletion, and around 75% of these changes are reversed by the inhibition of EZH2 activity (Figure 3C and Supplementary Tables S1A and S2).…”
Section: Absence Of Tks4 Induces Invasion Through Ezh2 Hyperactivitymentioning
confidence: 99%